ECONOMIC-STATISTICAL ANALYSIS OF DEVELOPMENT OF HIGHER PROFESSIONAL EDUCATION IN RUSSIA - Sergey V. Ivanov (Статистика и экономика, 2016)
This article gives the economic-statistical analysis of the development of higher professional education, shows its role in Russian economy and dynamic of number of university-educated employees. The government-owned and non-government institutions of higher professional education, the issue of its funding, and its use in educational process of electronic tutorials are studied.